Joint kinetic demand for performance in high jump - Fujimori, T.; Tobe, N.; Sado, N. (Sports Biomechanics, 2024)
High jump is a power-demanding motor task. Jumpers extend the take-off leg joints with maximum effort, but kinetic requirements (i.e. torque/power) for each joint are unclear. Here we show the inter-joint differences in the kinetic exertion related to the flight height in high jump trials by 16 male high jumpers (personal best record: 1.90-2.35 m). For the knee joint, both maximum net power and maximum norm of torque were significantly and positively correlated with flight height, with a stronger correlation for maximum net power (r = 0.70) than for maximum norm of torque (r = 0.52). For the hip joint, maximum norm of torque was significantly correlated with flight height (r = 0.62), but maximum net power (r = 0.36) was not. Both torque and power exhibited the proximal-to-distal sequence (from hip to ankle). The norm of ground reaction force peaked almost simultaneously with the hip torque while external net power peaked with knee power. We suggest that the required musculoskeletal function of each joint differs even in the same task. We suggest that it may be effective to adapt the different training programme between joints to improve performance. Jumpers should prioritise torque exertion for the hip and power exertion for the knee.